"RUANG KOPDAR" AT TANJUNG PRIOK STATION AS RAJUTKEJUT SPACE OF JOY IN CIRCUIT OF CULTURE STUDIES - Wulandari, Sari (Srawung: Journal of Social Sciences and Humanities, 2024)
Pekan Kebudayaan Nasional 2023 (PKN 2023) was held from 20 to 29 October 2023 in various areas in Jabodetabek. Researcher observed the Tanjung Priok Station and found that the RajutKejut community had created a lounge area known as "Ruang Kopdar." This research aims to uncover the meanings behind the work "Ruang Kopdar" created by the RajutKejut community. The research was conducted qualitatively through observations, interviews, and literature studies. The cultural phenomenon of RajutKejut will be analyzed using a cultural studies approach to uncover its meaning. Stuart Hall and Paul du Gay introduced the Circuit of Culture, a model for analyzing and interpreting cultural phenomena. This model identifies five elements of cultural practice: representation, production, consumption, identity, and regulation. The research findings revealed that RajutKejut's installation "Ruang Kopdar" at Tanjung Priok Station transforms the building's cold, gloomy atmosphere into a warmer, more inviting space. This contrast highlights the hot climate and challenging lives of the area's residents. The installation fosters a dynamic interplay between creation and enjoyment, where production and consumption meet to create joy. Researcher perceive "Ruang Kopdar" as a space where expression and existence converge, providing a meaningful contribution that restores a sense of humanity and satisfies fundamental social needs.